The plyometric treatment effects on change of direction speed and reactive agility in young tennis players: a randomized controlled trial - Sinkovic, Filip; Novak, Dario; Foretic, Nikola; Kim, Jinseo; Subramanian, S. V. (Frontiers in Physiology, 2023)
Aim: The aim of this paper is to determine the effect of six weeks of plyometric training on speed, explosive power, pre-planned agility, and reactive agility in young tennis players. Methods: The participants in this study included 35 male tennis players (age 12.14 ± 1.3 years, height 157.35 ± 9.53 cm and body mass 45.84 ± 8.43 kg at the beginning of the experiment). The biological age was calculated and determined for all participants. 18 of the participants were randomly assigned to the control group, and 17 were assigned to the experimental group. Running speed (sprints at 5, 10, and 20 meters), change of direction speed (4x10 yards, 20 yards, T-test, TENCODS), reactive agility (TENRAG), and explosive power (long jump, single leg triple jump, countermovement jump, squat jump, and single leg countermovement jump) were all tested. The Mixed model (2x2) ANOVA was used to determine the interactions and influence of a training program on test results. Furthermore, Bonferroni post hoc test was performed on variables with significant time*group interactions. Results: The results of this research indicate that an experimental training program affected results in a set time period, i.e. 5 out of total 15 variables showed significant improvement after experimental protocol when final testing was conducted. The experimental group showed significantly improved results in the 5m sprint test in the final testing phase compared to the initial testing phase, this was also the case in comparison to the control group in both measurements. Furthermore, the experimental group showed significant improvement in the single leg countermovement jump in the final test, as well as in comparison to the control group in both measurements. The change of direction speed and reactive agility test also exhibited significant improvement in the final testing phase of the experimental group. Conclusion: The results of this research indicated that a six-week program dominated by plyometric training can have a significant effect on the improvement of specific motor abilities within younger competitive categories. These results offer valuable insights for coaches in designing diverse tennis-specific scenarios to enhance overall performance, particularly focusing on the neuromuscular fitness of their players.